Compliance programs, signaling and firms' international coordination - Daniel Herold (Philipps-University Marburg, School of Business and Economics, 2017)
Fines imposed on firms for corporate infringements such as cartels reduce these infringement's profitability. When a manager knows when a violation is unprofitable he can prevent violations committed by an uninformed employee by investing in compliance programs (CPs). Investments can be interpreted as signals. The paper shows that there exists a separating equilibrium where high investments in CPs induce the employee to obey the law. However, if CPs are too expensive the signal is not credible. The manager can also show personal commitment to compliance ('tone-at-the-top'). Coordination on an efficient outcome will then be achievable if commitment is costly. Imposing high, individual sanctions on the manager disturbs a firm's internal coordination because he is unable to credibly signal that an infringement does not pay off for the firm. However, imposing sanctions on the employee unambiguously deters violation.
Keywords: D82; D86; L14; L22; K20; K21; 330; Compliance; Crime; Tone-at-the-top